Isolamento bioguiado dos compostos adstringentes do pedúnculo de caju - Mendes, Liana Maria Ramos (2019)
Despite its nutritional richness and high functional activity, the cashew still presents a low consumption due to the astringent flavor present in its pulp. To solve the problem of astringency, it is necessary to identify the compounds present in the cashew apple that are responsible for this characteristic. An attractive tool to identify and isolate compounds is liquid chromatography, the combination of this instrumental analysis with the biological (bioguided) response led to the discovery of several compounds responsible for the sensorial characteristics of foods. This work had as objective to isolate and identify the components of the cashew apple responsible for its astringency. The clone used was the CCP09 from the experimental field of the EMBRAPA of Pacajus. The cashew apples were sanitized, freeze-dried and ground. The ground sample underwent a methanolic extraction in bath ultrasound, taking the methanolic extract of cashew apple (EC) as the product. Protein precipitation was performed with the EC and BSA to obtain the astringent compounds. After precipitation, the phenolics present in the precipitate were extracted with methanol in bath ultrasound, taking the protein precipitate extract of cashew (EP) as the product. The identification of the compounds was performed by UPLC-QTOF MSE. The sensorial test was carried out with the objective of measuring the astringency intensity in the analyzed samples. This attribute was measured on a 5-point scale (0: non astringent and 4: extremely astringent), where the samples of EC, EP, anacardic acid mixture and their fractions isolated in HPLC-UV / VIS were analyzed. The identification of the compounds revealed the presence of flavonoids and anacardic acids in both the EC and EP. In the sensorial tests EP resulted in an average of 2.5, considered astringent- very astringent in the scale of 5 points. A mixture of anacardic acids, had an average of 1.76, considered astringent in the scale of 5 points. With a positive (bioguided) sensory response to the astringency perception in anacardic acids, their fractions were analyzed sensorially. Given the results it is possible to conclude that the anacardic acids contribute to the astringency in the cashew apple, being the anacardic acid 15:3 more astringent when compared to the 15:1.